2005
DOI: 10.1029/2005gl023875
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variation of shear‐wave splitting across an active fault and its implication for stress accumulation mechanism of inland earthquakes: The Atotsugawa fault case

Abstract: We analyzed shear‐wave splitting of small earthquakes around the Atotsugawa fault, central Japan, to infer a spatial variation in the direction of maximum horizontal compression (Shmax). While the angle, ϕ, between the Shmax direction and fault strike ranges approximately from 55° to 80° at the stations 2 to 8 km from the fault, it approaches 45° at the stations within 1 km from the fault. The present result indicates the local stress accumulation due to the localized flow or slip along the deep extension of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
47
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 15 publications
5
47
0
Order By: Relevance
“…5.1 Comparison with previous studies on focal mechanisms Stress field in the northern Hida region including the Atotsugawa fault zone has been investigated by Mikumo et al (1985Mikumo et al ( , 1988, Koizumi et al (1993), and Wada et al (2003) on the basis of focal mechanism data. Mikumo et al (1985Mikumo et al ( , 1988 showed that focal mechanisms along and westward extension of Atotsugawa fault are mostly strikeslip with ENE-WSW trending nodal planes.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…5.1 Comparison with previous studies on focal mechanisms Stress field in the northern Hida region including the Atotsugawa fault zone has been investigated by Mikumo et al (1985Mikumo et al ( , 1988, Koizumi et al (1993), and Wada et al (2003) on the basis of focal mechanism data. Mikumo et al (1985Mikumo et al ( , 1988 showed that focal mechanisms along and westward extension of Atotsugawa fault are mostly strikeslip with ENE-WSW trending nodal planes.…”
Section: Discussionmentioning
confidence: 89%
“…Mikumo et al (1985Mikumo et al ( , 1988 showed that focal mechanisms along and westward extension of Atotsugawa fault are mostly strikeslip with ENE-WSW trending nodal planes. Outside the Atotsugawa fault zone, they found reverse faulting events in the northwestern part and normal faulting events in the northern part.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations